HUBUNGAN KEPUASAN KERJA DENGAN KINERJA PERAWAT DI RUMAH SAKIT X KOTA BATAM TAHUN 2024 - Ririn Dwi Aneja; Didi Yunaspi; Desy Desy (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Globally, the performance of nurses in Sudan Hospital amounted to (32%) and the performance of nurses' duties in Malaysia only amounted to (27.5%). While in Indonesia, the performance of nurses in the low category as much as (48.2%) in Arosuka Hospital and at RSUD Dr. Sayidiman Magetan the performance of nurses in the good category is only (33%). Some of these studies show that nurse performance is still in the category of not optimal. Nurse performance is influenced by nurse job satisfaction. Organizations with high employee job satisfaction tend to have optimal performance. This study aims to determine the relationship between job satisfaction and the performance of inpatient room nurses at X Hospital, Batam City in 2024. This study used quantitative research with analytic design and cross sectional approach to 91 inpatient room nurses at X Hospital Batam City Year 2024. This research was conducted from July 29 to August 23, 2024. Sampling using total sampling technique. The measuring instrument in this study used a questionnaire. The results of job satisfaction in the satisfied category were 63 nurses (69.2%) and average performance was 32 nurses (35.2%). Data analysis used is the spearman correlation test. The test results obtained r=0.226 with a p value of 0.0310.05 which means H0 is rejected and Ha is accepted. So it can be concluded that there is a weak and significant relationship between Job Satisfaction and the Performance of Inpatient Room Nurses at X Hospital Batam City in 2024. Hospital management can maximize nurse performance by paying attention to nurse satisfaction such as providing awards, promotions, and salaries that meet expectations, especially for non-civil servant nurses in order to create optimal nurse performance. Keywords: job satisfaction, performance, nurse